Association of paternal cadmium and other heavy metal exposure to birth outcomes using propensity score matching. (January 2023) - Lee, Yu Min; Kim, Yangho; Park, Hyesook; Hong, Yun-Chul; Ha, Mina; Kim, Young Ju; Ha, Eun Hee
Abstract: Background: Human exposure to cadmium has various effects on health, especially on male reproductive organs. Although it is widely known that prenatal maternal cadmium exposure can affect birth outcomes, the effect of paternal exposure to cadmium remains unclear. Objectives: This study aimed to evaluate the effect of paternal cadmium exposure on fetal growth by considering maternal cadmium exposure and exposure to other heavy metals, namely mercury and lead. Methods: The Mothers and Children's Environmental Health (MOCEH) study is a prospective birth cohort study in Korea. Overall, 1313 families (father-mother-child triple) without child abnormalities and who completed paternal whole blood cadmium assessments were included in this study. Families were divided into two subgroups based on the blood sampling periods, namely early and late pregnancy. Subjects were selected as follows: one family triple with a high level of paternal cadmium and two triples with low levels of paternal cadmium, using the method of propensity score matching. And linear regression analyses were performed. Results: The group with high paternal cadmium exposure (80% or more; 1.93 μg/L) had lower birth weight infants compared to the group with low cadmium concentrations (β(se) = −0.21(0.10); p-value = 0.0283). After stratification by infant sex, prenatal paternal cadmium exposure significantly reduced the birth weight of females in subgroups of different sampling times, namely early pregnancy (β(se) = −0.52 (0.22); p-value = 0.0170) and late pregnancy (β(se) = −0.43 (0.18); p-value = 0.0160). Finally, after performing propensity score matching in the early pregnancy measurement group, it was found that the prenatal exposure of father to cadmium significantly reduced birth weight in females (β(se) = −0.72(0.25); p-value = 0.0047). Conclusion: This study assessed the effect of paternal cadmium exposure on birth outcomes in family units consisting of a father, mother, and child. Prenatal paternal cadmium exposure negatively affected birth weight, especially that of female, considering covariates and other heavy metals exposure, namely mercury and lead. Graphical abstract: Image 1 Highlights: Paternal cadmium exposure was associated with birth weight reduction, using PSM. Prenatal paternal cadmium exposure is associated with reduced the birth weight in females only. This study is the first report about paternal cadmium exposure and birth outcomes.